Some Irregular Forms of the Elegiac Distich - Smith, Kirby Flower (Gorgias Press, 2009)
Kirby Flower Smith explores the development of Greek and Latin elegiac meter from its origins to Imperial Rome
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: POETRY / Ancient & Classical